Direct torque control permanent magnet synchronous motor drive with asymmetrical multilevel inverter supply - Abdul Kadir, M.N.; Mekhilef, Saad; Ping, H.W. (2008)
This paper demonstrates the Direct Torque Control Permanent Magnet Synchronous Motor (DTC-PMSM) drive fed by asymmetrical multilevel inverter. The cascaded H-bridges topology with ratio-3 dc voltage sourced cells inverter has been employed. The DTC controller receives a reference torque and flux signals, the torque controller output determines the position of the desired flux vector. The amplitude of this vector is determined by the reference flux amplitude. The reference voltage vector is calculated as a continuous value using a technique developed originally for the SVM controlled drive. In this study, however, the reference voltage vector has been approximated to the nearest voltage vector achievable by one switching state of the multilevel inverter. The performance of two- and three-cells per arm inverter drives has been compared to that of the SVM-inverter drive at two values of the switching intervals. The results reflect the low switching frequency and torque ripple advantages of the proposed scheme.